Cutis Marmorata Telengiectatica Congenita with Kimura's Disease and Nephrotic Syndrome as a Sequele to Membranoproliferative Glomerulonephritis - Shruta Melissa; Ramesh Bhat; Jacintha Martis (Wolters Kluwer Medknow Publications, 2024)
Cutis marmorata telangiectatica congenita (CMTC) is a rare capillary malformation characterized by persistent reticulated marbled erythema. A 16-year-old boy presented with reddish net-like lesion over the left side of his body which was initially noticed at the age of three, with slight fading over the years which did not disappear on local warming. On examination, he had nonblanchable, reticular erythema over the left side of the body, not crossing the midline. After complete evaluation, a diagnosis of CMTC was made. CMTC has been associated with musculoskeletal anomalies, vascular abnormalities, cardiac defects, neurological defects, and ocular anomalies. Once CMTC is diagnosed, it is crucial to identify and manage any associated anomalies through a multidisciplinary approach. Additionally, the patient was also diagnosed with Kimura's disease and nephrotic syndrome secondary to membranoproliferative glomerulonephritis.